TATRC Reserve Medical Component Training (RCT) Case Scenarios - Leo Kobayashi; Marc Shapiro; Kenneth Williams; John Morey; Timothy Counihan (Association of American Medical Colleges, 2009)
Abstract This simulation case is a fully interactive manikin-based simulation scenario modular package for combat casualty care training of military medical personnel. The resource contains two single-patient scenarios and one multicasualty scenario, as well as manikin programming and supplemental materials. In the case, a radio call from a field medic alerts the team that a patient is coming in 5 minutes. The patient is a 15-year-old male goatherd who stepped on a land mine while tending to goats. The accident occurred 3 hours ago, and the patient is being transported by pickup truck to the forward surgical teams, but the medic just got in radio range. Both forward surgical team surgeons are in the village meeting with village elders, so a driver is dispatched to bring them back. The field medic reports he applied a makeshift tourniquet to the leg. This scenario has been used with three US Army Reserve Component units between 2005 and 2006.